Presenilin proteins undergo heterogeneous endoproteolysis between Thr291 and Ala299 and occur as stable N- and C-terminal fragments in normal and Alzheimer brain tissue - Podlisny, M B; Citron, M; Amarante, P; Sherrington, R; Xia, W; Zhang, J; Diehl, T; Levesque, G; Fraser, P; Haass, C; Koo, E H; Seubert, P; et al. (Neurobiology of disease, 1997)
Humans inheriting missense mutations in the presenilin (PS)1 and -2 genes undergo progressive cerebral deposition of the amyloid beta-protein at an early age and develop a clinically and pathologically severe form of familial Alzheimer's disease (FAD). Because PS1 mutations cause the most aggressive known form of AD, it is important to elucidate the structure and function of this multitransmembrane protein in the brain. Using a panel of region-specific PS antibodies, we characterized the presenilin polypeptides in mammalian tissues, including brains of normal, AD, and PS1-linked FAD subjects, and in transfected and nontransfected cell lines. Very little full-length PS1 or -2 was detected in brain and untransfected cells; instead the protein occurred as a heterogeneous array of stable N- and C-terminal proteolytic fragments that differed subtly among cell types and mammalian tissues. Sequencing of the major C-terminal fragment from PS1-transfected human 293 cells showed that the principal endoproteolytic cleavage occurs at and near Met298 in the proximal portion of the large hydrophilic loop. Full-length PS1 in these cells is quickly turned over (T1/2 approximately 60 min), in part to the two major fragments. The sizes and amounts of the PS fragments were not significantly altered in four FAD brains with the Cys410Tyr PS1 missense mutation. Our results indicate that presenilins are rapidly processed to N- and C-terminal fragments in both neural and nonneural cells and that interference with this processing is not an obligatory feature of FAD-causing mutations.